STRATEGI PEMBELAJARAN PEMBERDAYAAN KEMAMPUAN BERPIKIR DI SDN 26 MATARAM - Gusfian, Mauliana; Sahsiani, Melia; Islami, Nanda Intan; Madani, Nurhasobah; Hidayah, Nurul; Latifah, Nurul; Istiningsih, Siti; Putri , Hikmah Ramdhani (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe the thinking empowerment learning strategy implemented by a sixth-grade teacher at SDN 26 Mataram. The strategy is carried out through Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models, which encourage students to think critically, creatively, and reflectively. The teacher acts as a facilitator who creates an active and engaging learning atmosphere. This research uses a qualitative approach with observation, interviews, and documentation as data collection methods. The findings reveal that the strategy effectively increases student engagement, deepens conceptual understanding, and fosters independent learning. Despite challenges such as time constraints and preparation of learning media, the teacher overcomes them through reflection and effective time management Keywords: Learning Strategy, Critical Thinking, Independent Curriculum